Flexural Behavior of Epoxy Matrix Composites Reinforced with Malva Fiber - Margem,Jean Igor (2015)
Polymer composites reinforced with natural fibers have been increasingly investigated and applied as engineering materials owing to their economical, technical, societal and environmental advantages. The malva fiber, particularly an important resource in the Amazon region in Brazil, only recently begin to be investigated as possible composite reinforcement for engineering application. However, the mechanical properties of composites reinforced with malva fiber are still unknown. In this paper, the flexural behavior of epoxy matrix composites reinforced with continuous malva fiber was for the first time investigated. Specimens of continuous malva fibers aligned along an epoxy matrix were press-molded. Three-points bending test were performed and the fractured specimens were analyzed by SEM. The results showed a marked improvement in the composites flexural properties with the increase in the amount of reinforced malva fiber. This improvement was found to match the Rule of Mixtures, which revealed the unique potential of malva composites for engineering applications.